Modelling Inflation Rates Volatility in Alegria Using ARCH Models. - BOUDAB, Siham; BEN DJEDDOU, SAMI (Finance and Business Economies Review, 2020)
This paper aims to modeling the inflation rates in Algeria using the ARCH model during the period January 2000 to December 2018. The results show that the GARCH (1.1) model is the best in modeling and forecasting Algerian’s monthly rates of inflation.